2010 Conference Record of the Forty Fourth Asilomar Conference on Signals, Systems and Computers 2010
DOI: 10.1109/acssc.2010.5757551
|View full text |Cite
|
Sign up to set email alerts
|

A normalized least mean fourth algorithm with improved stability

Abstract: The paper presents a new normalized least mean fourth (NLMF) algorithm. The algorithm is derived through the minimization of the mean fourth normalized estimation error. The main advantage of the algorithm with respect to the available NLMF algorithms is that it remains stable as the input power of the adaptive filter increases. A stability step size bound of the proposed algorithm is derived. The step size bound depends on the weight initialization, while it does not depend on the input power of the adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…To deal with this problem, we also proposed a normalized version of SSLMF which is designed using the concept of a recently introduced normalized LMF [36] variant that is proven to be stable under any circumstances. Consequently, by employing the concept of [36], it can be shown that the stable normalized version of the proposed SSLMF algorithm is given by following recursion…”
Section: Derivation Of Proposed Sslmfmentioning
confidence: 99%
“…To deal with this problem, we also proposed a normalized version of SSLMF which is designed using the concept of a recently introduced normalized LMF [36] variant that is proven to be stable under any circumstances. Consequently, by employing the concept of [36], it can be shown that the stable normalized version of the proposed SSLMF algorithm is given by following recursion…”
Section: Derivation Of Proposed Sslmfmentioning
confidence: 99%
“…In [15]- [17], it is shown that the stability of the algorithms (8) and (9) depends on the mean square input of the adaptive filter. This is due to the fact that (2) implies that in both (8) and (9), the numerator of the weight vector update term is fourth order in , while the denominator is second order in .…”
Section: Problem Formulationmentioning
confidence: 99%
“…Due to (25), (28) and (29), has an upper bound that depends on the noise only through its variance . Due to (37) and (15), the highest power of under the expectation sign in the upper bound of is 2. Consequently, conditions on noise moments with order higher than 2 are not needed for the boundedness of the MSD of NLMF4.…”
Section: A Bounding Recurrence Of the Msdmentioning
confidence: 99%
See 2 more Smart Citations